IMPLEMENTASI PROGRAM TEMPAT PENGELOLAHAN SAMPAH (TPS) 3R (REDUCE, REUSE, RECYCLE); Studi Kasus Desa SedatiGede Kecamatan Sedati Sidoarjo - Adinda Binuuril Qur’an Al-Haq; Hendra Sukmana (Journal Publicuho, 2025)
This study aims to analyse the implementation of waste management at BUMDes Berdikari Abadi in the TPS 3R program in SedatiGede Village. The research methodology used in this study is qualitative. The informants of this study were the Head of BUMDes, Head of BUMDes Operations, Head of BUMDes Administration, Village Head, and community users of TPS 3R. The data sources used were documents, observations, and interviews. Data analysis used Edward III. The results of the study showed that there were four (four) factors that influenced the implementation of waste management in the TPS 3R Program at BUMDes Berdikari Abadi in SedatiGede Village. This waste management program is running well. The managers and personnel of TPS 3R have carried out their duties and obligations properly in accordance with the established procedures. d) Bureaucratic structure, standard operating procedures (SOP) have been established in accordance with the provisions set. Waste management is running well, with each party carrying out its duties and responsibilities in accordance with laws and regulations.